Murine cytomegalovirus interacts with major histocompatibility complex class I molecules to establish cellular infection. - Wykes, M N (1993)
The expression of stable, correctly folded major histocompatibility complex class I molecules conferred susceptibility to murine cytomegalovirus (MCMV) in cells which were previously resistant to infection, demonstrating that these molecules interact critically with MCMV to initiate infection. All class I molecules could potentiate MCMV infection but H-2Dd and Kb molecules were most efficient. Monoclonal antibodies specific for the alpha 1 and/or alpha 2 domains of Dd and Kb inhibited infection. Infection of L cells transfected with hybrid major histocompatibility complex class I molecules demonstrated that allelic control of susceptibility to MCMV mapped to the alpha 1 domain of Dd when in correct configuration with the alpha 2 and alpha 3 domains. In MCMV-resistant RMA-S cells, an improvement in the conformation of class I molecules introduced susceptibility to infection.